Antinociceptive effect of lupeol: evidence for a role of cytokines inhibition - Lima, Flávia Oliveira de (2012)
Fundação Oswaldo Cruz. Centro de Pesquisa Gonçalo Moniz. Salvador, BA, Brasil / Universidade Estadual de Feira de Santana. Feira de Santana, BA, Brasil